Integrated development and optimisation of an organic acid-based hydrometallurgical process for treatment of spent lithium-ion batteries (LIBs) - Jeza, Sabelo Acceptance (Stellenbosch : Stellenbosch University, 2022)
Thesis (MEng)--Stellenbosch University, 2022.